Análise do retorno econômico de investimentos de distribuição considerando a atuação regulatória no setor elétrico brasileiro - Fabian, Maria Eva Gaspar de Queiroz (2008)
The adoption of guidelines defined by the Brazilian Electric Sector Restructuring RESEB project has created a regulatory model that adopts a price cap tariff system which focuses on the efficiency and quality of the service rendering and tariff systems as well as imposing very strict regulation. The traditional analysis of return on investment used by utilities is no longer appropriate as it fails to take into account changes that occur in project payment due to periodic tariff revision, when factor X is defined for the basis of the payment. In this context, energy distribution companies have to reevaluate their models of analysis for return on investment so as to contemplate the effects caused by the new regulatory scenario, in the search for shareholder profitability maximization. This work analyzes the impact of this regulatory model on discounted cash flow revenue used to calculate financial returns. First a general overview of project viability and the methods applied in these analyses are presented, then how these methods can be used in the electric sector. The history behind the establishment of the rules for tariff change and their relationship with investments is examined and a historical retrospective of the legislation relating to the Brazilian electric sector is presented, as well as some theoretical aspects of economic regulation. The analysis of results from a case study carried out in an electric energy distribution company, in which cash flows are simulated using traditional methods to determine revenue and compared with cash flow from the regulatory perspective using a different approach of revenue for the periods prior to and post tariff revision are presented. It is possible to infer that in the current scenario a distribution company should incorporate studies into the impacts provoked by the X factor in efficiency gains, and should develop strategies to minimize the risks that can result from these differences.